2021
DOI: 10.1039/d1dt00071c
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of phospha–Wittig reagents towards NHCs and NHOs

Abstract: Phospha–Wittig reagents of the type RPPMe3 can be considered as phosphine-stabilized phosphinidenes and were shown to react with NHCs and NHOs to afford NHC phosphinidene adducts or P-substituted NHOs, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

7
1

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 50 publications
1
37
0
2
Order By: Relevance
“…12 kcal mol À1 . 17 Reactivity of cyanophosphines towards B(C 6 F 5 ) 3 4a-c possess two potential binding sites for Lewis acids, the LPs on P and N, even though steric congestion should render the phosphorus rather inaccessible. By reacting 4a-c with B(C 6 F 5 ) 3 , the rst examples of the corresponding phosphanitrilium borates RP(H)CNB(C 6 F 5 ) 3 (R ¼ Mes* (5a), R ¼ Mes Ter (5b), R ¼ Dip Ter (5c)) were prepared (Scheme 4).…”
Section: Formation Of Cyanophosphines Starting From 3a-cmentioning
confidence: 99%
See 1 more Smart Citation
“…12 kcal mol À1 . 17 Reactivity of cyanophosphines towards B(C 6 F 5 ) 3 4a-c possess two potential binding sites for Lewis acids, the LPs on P and N, even though steric congestion should render the phosphorus rather inaccessible. By reacting 4a-c with B(C 6 F 5 ) 3 , the rst examples of the corresponding phosphanitrilium borates RP(H)CNB(C 6 F 5 ) 3 (R ¼ Mes* (5a), R ¼ Mes Ter (5b), R ¼ Dip Ter (5c)) were prepared (Scheme 4).…”
Section: Formation Of Cyanophosphines Starting From 3a-cmentioning
confidence: 99%
“…Recently, we have revisited the chemistry of phosphanylidene phosphoranes, so-called phospha-Wittig reagents, ArPPMe 3 ( 1a–c ) ( 1a : Ar = Mes*; 1b : Ar = 2,6-(2,4,6-Me 3 C 6 H 2 )–C 6 H 3 , Mes Ter, 1c : Ar = 2.6-(2,6- i Pr 2 C 6 H 3 )–C 6 H 3 , Dip Ter). 17 We successfully used them as phosphinidene transfer reagents in reactions with N-heterocyclic carbenes (NHCs) or N-heterocyclic olefins (NHOs), 17 towards Al( i ) species to give phosphaalumenes, 18 and with Cp 2 Ti(C 2 (SiMe 3 ) 2 ) to afford terminal titanium phosphinidene complexes, respectively. 19 In this contribution, the reactivity of the phospha-Wittig reagents 1a–c towards isocyanides is presented ( Scheme 1 , bottom), giving a series of 1,3-phosphaazaallenes.…”
Section: Introductionmentioning
confidence: 99%
“…As a synthetic entry we chose the titanocene precursor [Cp2Ti(btmsa)] (1), 23,24 in combination with the phospha-Wittig reagents Mes*PPMe3 (2a), Mes TerPPMe3 (2b) and Dip TerPPMe3 (2c) (Scheme 2). 25 In analogy to the synthesis of IV using 2b in conjunction with Cp2Zr(PMe3)2, 20 we first studied the formal ligand exchange reaction btmsa for PAr between 1 and 2 to give [Cp2Ti(PMe3)PAr] in-silico to evaluate its thermodynamic feasibility. For all three combinations an exergonic Gibbs Free Enthalpy change to give the complexes [Cp2(PMe3)Ti=PAr)] according to equation 1 (RG  = −5.8 (2a), −11.2 (2b), −9.0 (2c) kcal•mol −1 , Eq.…”
Section: S3mentioning
confidence: 99%
“…[15] Since the first reports by Burg and Mahler in the 1960s, [16,17] a number of stable, mostly aryl-substituted or acenaphtene-based, metal-free phosphanylidene-σ 4 -phosphoranes have been reported. [8,[18][19][20][21][22][23] Aryl-substituted variants have been first described by Protasiewicz and co-workers and it was shown that these systems cleanly react with aldehydes to generate phosphaalkenes akin to the formation of alkenes in the classical Wittig reaction. [8] In addition, phosphanylidenephosphoranes show phosphinidene-like reactivity, which was demonstrated by a series of ligand-deconstruction reactions and diphosphene (RP)2 formation upon photochemically-induced PMe3 release in Ar−P(PMe3) (Ar = Mes*, Mes Ter, Tip Ter).…”
Section: Introductionmentioning
confidence: 99%
“…[18,[24][25][26][27] This phosphinidenoid-type reactivity was revisited by our group and we could convincingly demonstrate that PMe3 can readily be liberated upon addition of a stronger Lewis-base. For instance, an N-heterocyclic carbene (NHC), N-heterocyclic olefin (NHO) or isocyanate for PMe3 exchange yielded NHC phosphinidene adducts, [21] C(sp 2 )-H activated P-substituted NHOs [21] or 1,3phosphaazaallenes, [28] respectively. The latter were shown to be facile precursors for cyanophosphines.…”
Section: Introductionmentioning
confidence: 99%